If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(y+6)=3y-y
We move all terms to the left:
2(y+6)-(3y-y)=0
We add all the numbers together, and all the variables
2(y+6)-(+2y)=0
We multiply parentheses
2y-(+2y)+12=0
We get rid of parentheses
2y-2y+12=0
We add all the numbers together, and all the variables
12!=0
There is no solution for this equation
| 7n^2-4=59 | | 5r+11=96 | | 12x-78=8x-46 | | 5/3x+1/3x=7/3+7/3x | | 2h+12=4h | | 3x^2+x+17=9 | | 4280=2300+60c | | 6x+15=6(x-30 | | 3(n-5)=-4n+13 | | -2y-(-5)=3y-9 | | (.75x+.5)=540 | | -5x+29=-9x+45 | | −4x+6=9x−8 | | 23=-8+x | | m/4+6=(-1) | | 4s^2-2=-26 | | 35i+10=290 | | 16t^2+56t+70=0 | | 5(k-84)=-10 | | (3/4x1/2x)=540 | | 4x2+16x+8=0 | | -8-3x=86-2x | | 12=w4+ 10 | | 3p^2=-60 | | 5x2−27x+10=0. | | 15n-12=3(14+3n)-12 | | 8d+2=90 | | 15n+60=105 | | -2n+5=3n+25 | | -1x^2+5.76=0 | | 323=-8(7x+2)+3 | | 18=2r+4 |